Overexpression of RelA/SpoT homologs, PpRSH2a and PpRSH2b, induces the growth suppression of the moss Physcomitrella patens. Issue 1 (2nd January 2015) - Sato, Michio; Takahashi, Tomohiro; Ochi, Kozo; Matsuura, Hideyuki; Nabeta, Kensuke; Takahashi, Kosaku
Abstract: Two genes encoding RelA/SpoT homologs, PpRSH2a and PpRSH2b, which are involved in the synthesis of bacterial alarmone guanosine 5′-diphosphate 3′-diphosphate (ppGpp) for the stringent response, were isolated from the moss, Physcomitrella patens . A complementary analysis of PpRSH2a and PpRSH2b in Escherichia coli showed that these genes had ppGpp biosynthetic activity. The recombinant PpRSH2a and PpRSH2b were also shown to synthesize ppGpp in vitro . Both proteins were localized to the chloroplasts of P. patens. Expression of the PpRSH genes was induced upon treatment with abscisic acid or abiotic stresses, such as dehydration and UV irradiation. Overexpression of PpRSH2a and PpRSH2b caused suppression of the growth in response to 1% (w/v) of glucose. The present study suggests the existence of a mechanism to regulate the growth of P. patens, which is governed by plant RSH in chloroplasts Graphical abstract: : Functional analysis of RelA/SpoT homologues ( RSHs ) suggests the existence of a mechanism to regulate the growth of P. patens, which is governed by ppGpp in chloroplasts.